Is It Obesity or Metabolic Syndrome Which Has a Greater Prevalence ToCause Muscoloskeletal Complaints? A Cross Sectional Study in theCepokomulyo District, Malang Regency - Perdana Aditya Rahman (Indonesian Journal of Rheumatology, 2024)
Introduction: Musculoskeletal (MSK) complaints including pain,swelling, stiffness, or immobility of joints and muscles are among themost common health issues that biomechanical factors are one of therisk factors. Metabolic syndrome is a combination of several riskfactors including obesity, hypertension, low HDL-C levels,hypertriglyceridemia, and impaired glucose tolerance. These issues areknown to influence the incidence of metabolic inflammation associatedwith several MSK diseases, in which obesity is one of the mainbiomechanical factors. Aim: To compare the Prevalence Odd Ratio(POR) of MSK complaints associated with metabolic syndrome (MetS)and obesity. Conclusion: This study included 260 patients, with 49.6%(n=129) of them having metabolic syndrome. The most common MSKcomplaint region was the right knee (n=85). MSK complaints were mostcommon in the group of patients with MetS and obesity (n=109),compared to the group with MetS or obesity alone. Prevalence OddRatio (POR) results show that Group III (group of patients with obesityand without MetS) has the highest prevalence of MSK complaints whencompared to the other three groups.